The Role of Prayer in Seeking Mercy and Guidance: Lessons from the Tafsir of Surah al-Fatihah - Fadhilah, Asa Nur; Nirwana, Andri (Maʿālim al-Qurʾān wa al-Sunnah, 2023)
This research underscores the paramount role of prayer in believers' lives, emphasising its significance as a direct means of communication with the Creator. Focused on Surah Al-Fatihah, the "Mother of the Quran," the study delves into prayer for seeking guidance and mercy. Rooted in the Quranic command to invoke Allah and highlighted by various scholars, prayer, according to tafsir, encompasses worship, seeking help, supplication, and ritual prayer. The research employs a literature review method to explore interpretations of Surah Al-Fatihah, contributing nuanced perspectives on prayer's role. Emphasising spiritual needs over worldly matters, the study offers valuable insights for enriching worship and deepening understanding. Because Surah Al-Fatihah is so important in Islamic worship and its ending is all about supplications, the study concludes that it was successful in giving a deep understanding of prayer in this basic Surah, which had an effect on daily life and spiritual connections.